Femme Fatale and Intertextuality, the Onomastics in the Poems of Raúl Gómez Jaittin: Medea and Electra - Chen Sham, Jorge (2020)
The Colombian poet Raúl Gómez Jattin (1945-1997), one of the most pristine and praised voices of Colombian poetry of the second half of the 20th century, published the book Of Love (1988), where he gathered a complex intertextuality based on the mythology and in the cultural history of mankind. I am interested in analyzing, in this article, two poems in which Gómez Jaittin gives free rein to that decadent conception of the femme fatale, thus revisiting the figures of Medea and Electra. His attention to precious detail and voluptuousness, which leads to sadism, make the vision of women closer to the poetry of the modernist Cuban Julián del Casal, who already proposed in his poetry such a figuration of an unhealthy and pungent eroticism.